SINERGI BISNIS DIGITAL DAN DIGITAL MARKETING DALAM MENINGKATKAN BRAND AWARENESS DI ERA GLOBALISASI - Yuliani, Sarah; Sasi Ramadhani, Nidya Calista; Putri Sentosa, Aura Nabila (Program Studi Magister Manajemen, Direktorat Pascasarjana, Universitas Sangga Buana, 2025)
In the age of globalization, the advancement of digital technology has prompted organizations to adopt digital strategies in their operations and marketing. Digital business synergy and digital marketing are essential components for enhancing brand awareness. Extensive research has been conducted on the synergy between digital business and digital marketing for brand recognition; however, studies focusing on MSMEs remain few. This study seeks to examine and elucidate the impact of digital business synergy and digital marketing on enhancing brand awareness in the context of globalization. This research employs a quantitative methodology utilizing a descriptive approach. Data was gathered via a questionnaire administered to 100 MSMEs in Sukabumi that have adopted digital business strategies and digital marketing, complemented by interviews to enhance comprehension of the issue under investigation. The analytical method employs multiple linear regression to ascertain the correlation between independent factors and brand awareness. The study's results indicate that the integration of digital business and digital marketing significantly impacts brand recognition, accounting for an influence of 68.1%. This research offers valuable insights for business stakeholders and government entities regarding the significance of digital transformation, serving as a reference for future studies in digital marketing and the digital economy.